Mujica - Campodónico, Miguel Angel, 1937- (Uruguay : Editorial Fin de Siglo, 2005)
Tomado de la contracubierta.
Keywords: MUJICA CORDANO, JOSE ALBERTO, -- 1934-; MOVIMIENTO DE LIBERACION NACIONAL (URUGUAY); MOVIMIENTOS REVOLUCIONARIOS -- URUGUAY; POLITICOS -- URUGUAY; URUGUAY -- POLITICA Y GOBIERNO -- 1985